2001
DOI: 10.1002/chin.200147110
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of 3‐(3,4‐Dimethoxyphenyl)‐1H‐1,2,4‐triazole‐5‐thiol and 2‐Amino‐5‐(3,4‐dimethoxyphenyl)‐1,3,4‐thiadiazole Derivatives Exhibiting Antiinflammatory Activity.

Abstract: Synthesis of 3-(3,4-Dimethoxyphenyl)-1H-1,2,4-triazole-5-thiol and 2-Amino-5-(3,4-dimethoxyphenyl)-1,3,4-thiadiazole Derivatives Exhibiting Antiinflammatory Activity.-A variety of the title triazole [cf. (III), (V)] and thiadiazole derivatives [cf. (VII), (X), (XI)] are synthesized and evaluated for their antiinflammatory activity. Some derivatives exhibit activity higher or similar to that of acetylsalicylic acid or ibuprofen. -(LABANAUSKAS, L.; KALCAS, V.; UDRENAITE, E.; GAIDELIS, P.; BRUKSTUS, A.; DAUKSAS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…An exhaustive investigation on different thiadiazole compounds have been done in recent years, many of which were found to posses wide spectrum of pharmacological actions. Moreover, various reports indicate that semicarbazides and thiadiazoles derivatives show anti-inflammatory (Labanauskas et al, 2001, Palaska et al, 2002 and analgesic (Amir and Shikha, 2004) activities. The present study was carried out to look into the anti-inflammatory activity of novel thiadiazole derivatives (7a-f) by different in vitro models for the first time.…”
Section: Anti-inflammatory Activity Of Novel Schiff Bases By In Vitromentioning
confidence: 99%
“…An exhaustive investigation on different thiadiazole compounds have been done in recent years, many of which were found to posses wide spectrum of pharmacological actions. Moreover, various reports indicate that semicarbazides and thiadiazoles derivatives show anti-inflammatory (Labanauskas et al, 2001, Palaska et al, 2002 and analgesic (Amir and Shikha, 2004) activities. The present study was carried out to look into the anti-inflammatory activity of novel thiadiazole derivatives (7a-f) by different in vitro models for the first time.…”
Section: Anti-inflammatory Activity Of Novel Schiff Bases By In Vitromentioning
confidence: 99%
“…It was reported that many thiadiazole and triazole derivatives have biological activity, with their antibacterial [15][16][17] and antifungal [18][19] action being notable. Recently researches were established an analgesic [20] and anti-inflammatory activity [21][22] for these heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives of triazoles, thiadiazoles and thiadiazines have played an important role in the medicinal chemistry, where they possess broad-spectrum antimicrobial activity 4,5 . Also they have been studied for a number of pathological conditions such as inflammation 6,7 , pain 8 10 , and hypertension 11 . Thus they can be used as stearic acid, a saturated fatty acid which has the same number of carbon atoms as oleic acid, was then appended to triazole, thiadiazole and thiadiazine nucleus, in order to combine the beneficial effects of the hetero cyclic nucleus and of the fatty acid in a new single structure of a certain biological activity on human health.…”
Section: Introductionmentioning
confidence: 99%